Establishment of two continuous adult stem cell lines from muscle and adipose tissues of rainbow trout (Oncorhynchus mykiss) for marbled fish meat production - Yaru Li; Ting Xue; Song Wang; Yue Zhang; Guoxiang Luan; Jinwu Wang; Huarong Guo (Aquaculture Reports, 2025)
Cell-cultured meat is an emerging technology with the potential to meet the nutritional needs, reduce environmental pollution and promote animal welfare. However, it is still a challenge to produce a marbled cell-cultured meat using the same species origin of muscle stem cells for protein production, and adipose-derived stem cells for fat production to enhance the texture, taste and tenderness. Here, we successfully established and characterized two continuous fish adult stem cell lines from rainbow trout (Oncorhynchus mykiss): muscle stem cell line (RTMS) and adipose-derived stem cell line (RTADS). These cell lines have maintained their myogenic/adipogenic potential over 50 and 30 times, respectively. Typically, muscle stem cells from fish species maintain their stemness for no more than 10 passages, while adipose-derived stem cells have not been previously established in fish. We optimized the differentiation media for RTMS cells, achieving differentiation and fusion indices of 35.89 % and 30.25 %, respectively, compared to the baseline medium which failed to induce differentiation. For RTADS cells, optimization of the differentiation medium significantly enhanced lipid droplet formation. Using 3D edible microcarriers, we produced marbled fat-containing cell-cultured fish meat of rainbow trout. The free amino acid and free fatty acid contents of the cell-cultured fish meat were found to be significantly higher than those of natural fish meat. This study provides two valuable seed cell lines for advancing cell-cultured fish meat production.